Effectiveness of Interactive Multimedia CD on Self-Care and Powerlessness in Hemodialysis Patients - 王魯梅(Lu-Mei Wang); 丘周萍(Chou-Ping Chiou) (The Journal of Nursing Research, 2011)
Background: Hemodialysis (HD) patients have low self-care knowledge, poor self-care behavior, and powerlessness. Purpose: The authors designed this study to, first, understand the current state of first-year HD patients' self-care knowledge, self-care behavior, and powerlessness and, second, assess the effectiveness of an interactive multimedia CD educational intervention. Method: A quasi-experimental, repeated measures design, with intervention and comparison groups, was used. All subjects for this study were recruited from six dialysis centers in southern Taiwan. The three points for outcome testing included baseline, 4 weeks, and 8 weeks. Research tools included an HD self-care knowledge questionnaire, an HD self-care behavioral questionnaire, a powerlessness questionnaire, and an interactive multimedia CD. Results: Results found that participants possessed insufficient knowledge, were incapable of completely achieving or comprehending routine self-care, and were affected by powerlessness. The interactive multimedia CD intervention effectively enhanced self-care knowledge (p＜.000) and self-care behavior (p＜.000) and improved powerlessness (p＜.000). Positive results persisted well after the conclusion of the intervention. Conclusions/Implications for Practice: Participants in the intervention group had better self-care knowledge and behaviors and feeling of control over their lives than those in the control group. This illustrates the positive effects of the interactive multimedia CD. Results demonstrate the potential benefits of using the interactive multimedia CD with elderly patients in HD and nursing practice education.